Pharmacist Occupational Features, Regulations Framework and Profession Enhancement Challenges of Pharmaceutics - Sulashvili, Nodar; Beglaryan, Margarita (Caucasus Journal of Health Sciences and Public Health, 2020)
An integral part of the state social security system is an implementation the citizens’ rights and protection Public health. The grade of the health care system partly relies on provision of the quality of pharmaceutical care services, which is largely dependent on the public pharmaceutical organizations’ personnel qualifications like pharmacists. In this regard, the professional qualification of pharmacists should be under the state control, and is one of the objects of the state regulation in the pharmaceutical field in particular, and the medical field in general; With the purpose to maintain the highest possible level of pharmacist specialists’ competences throughout with changing demands according professional qualification, which affecting on population’s health improvement. The modern system of pharmaceutical care is to improve the quality of life of patients’ promotion by highly skilled professionals in pharmacies, whose competence has been growing along the process of professional development. Pharmacist must not only be capable to use their knowledge and skills gained at the educational institutions, but also should be ready and motivated for the professional self-development, because without qualified pharmaceutical care there is no qualified health care system. Valuable studies aimed is to understanding perspectives of the pharmacist specialists’ professional aspect, which have not been carried out yet. Pharmacy is one of th